Synthesis of 2-Methyl/phenyl-3-[(4-substituted-benzylidene) Amino-phenyl]-6 & 8-disubstituted-1,3-quinazolin-4-ones as Potenital Anthelmintic Agents - S. Shukla, J.; Fadayan, M. (Asian Journal of Chemistry, 2010)
Thirty 2-Methyl/phenyl-3-[(4-substituted-benzylidene) amino-phenyl]-6&8-disubstituted-quinazoline-4-ones were synthesised and screened for their anthelmintic activity aganist Hymenolepis nanainfection in mice and Nippostrangylus brasilliensis infection in rat. Some of the compounds were also tested for their antiviral and antibacterial activity.